Factor Analysis of Youth Retention at Church: A Positioning of Adventist Higher Education Institution Students in Southern Asia Pacific Division - Hutabarat, Francis; Hutabarat, Franklin (Technium Social Sciences Journal, 2021)
This research aims to distinguish the factor of retention at Church in the Southern Asia Pacific Division Adventist Higher Education Institutions. Knowing these factors could help leaders in educational institutions to thoroughly plan their strategies to strengthen youth retention in Church. A set of the instrument of the questionnaire was acquired and distributed to student’s respondent at two higher education institution institutions in the Southern Asia Pacific Division Higher Education Institution namely Asia Pacific International University of Thailand, and Universitas Advent Indonesia of Indonesia. Exploratory factor analysis was used to distinguish the underlying dimensions that drive student satisfaction. Factor analysis pertaining to analysis on dimensions of Academic Courses. The results show that the KMO test is valued at 0.919 which is > 0.5; hence, the sample size is adequate for the analysis. On the other hand, the commonalities of all the variables are surpassing .4; consequently, all the variables are valuable in the model. The results show that factors in the analysis of student satisfaction on brand image and brand positioning at AIU and UNAI are that the courses helped them in: known nationally, maximum service, good reputation, provide health insurance, convenience registration process, provide scientific education & spiritual education, spiritual need.